Model competitive programme for students with disabilities at the ‘ready for labour and defence’ festival - Podberezko, N.A.; Lobastova, R.A.; Setyaeva, N.N.; Marchenko, A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop and justify a project for the All-Russian Physical Culture and Sports Complex ‘Ready for Labour and Defence’ (VFSK GTO) Festival among students with disabilities. Methods and structure of the study. An analysis of scientific literature, regulatory and legal acts, documentation of sporting events held under the VFSK GTO programme in the Altai Krai and modelling of VFSK GTO competitions for people with disabilities were applied. Results and conclusions. In order to achieve its goal, the All-Russian Physical Culture and Sports Complex ‘Ready for Labour and Defence’ needs to involve citizens with disabilities in competitive activities. The existing systems for evaluating competitive activities cannot be applied to the proposed Festival. The project allows students with disabilities from all nosological groups of the complex to participate. The Festival programme allows for its implementation in an inclusive approach.